Knowledge of elderly participants in character centers about hiv/aids (Research, Society and Development, 2020)
To evaluate the knowledge of elderly participants in community centers about HIV/AIDS. Cross-sectional and analytical study, carried out with elderly aged 50 years and over, participating in two social centers located in Brazil. Data collection took place in 2017, and a questionnaire was used for sociodemographic variables and the HIV questionnaire for the elderly. Associations were verified using the Chi-square and Fisher's exact tests. Results: 37 people participated and the female gender predominated. The concept, transmission, prevention and vulnerability domains presented a satisfactory evaluation in their entirety. Regarding treatment, many believe in curing the disease. A significant association was identified between the variable sex and sexual activity (p=0.002), age variable and the concept domains (p=0.045), transmission (p=0.031) and prevention (p=0.017). The variable condom use was associated with the transmission domain (p=0.036), and the sexual activity variable was associated with the transmission (p=0.054) and vulnerability (p=0.034) domains. Knowledge was unsatisfactory in terms of transmission and vulnerability, and satisfactory in relation to the other domains of the questionnaire.